Students’ Etiquette towards Teachers According to Syaikh Burhanuddin Az-Zarnuji - Pipin, Aep (Interdisciplinary Social Studies, 2021)
A deterioration in students' morality and etiquette in the classroom is a result of Indonesian education virtually losing its status as the study idol of the students. As a result, education becomes purely goal-oriented, with a singular focus on receiving a diploma. In actuality, one must first show respect to their teacher in order to learn, and then the effects might become apparent later. This study aims to: (1) Discover the concepts of students’ etiquette to teachers according to Syaikh Burhanuddin Az-Zarnuji in the book of Ta'lim Muta'allim Tariq At-Ta'allum in Fashl Ta'dzimul Ilmi wa Ahlih (2) Discover the pattern in learning about students’ etiquette to their teachers according to Syaikh Burhanuddin in the book of Ta'lim Muta'allim Tariq At-Ta'allum in Fashl Ta'dzimul Ilmi wa Ahlih. This study used a qualitative approach. The method used was descriptive. The data collection implemented was library research. The object being researched, as well as the data source, was the book Ta'alim Muta'alim by Syaikh Burhanuddin Az-Zarnuzi. The data collection method uses descriptive methods and the author performed content analysis. The results showed that students' etiquette towards teachers are students must always respect the teacher and the teacher's family, protect the rights of the teacher, do not walk in front of the teacher, do not sit in the teacher's place, do not start a conversation without the teacher’s permission, do not ask something when the teacher is bored, be on time, do not knock on the door of the teacher's house but be patient waiting for the teacher to come out.